Five new species of Turbonilla Risso, 1826 (Gastropoda, Heterobranchia, Pyramidellidae) found off the northeast coast of Brazil (02º-13º S) - Absalão, Ricardo Silva; Dos Santos, Franklin Noel; Tenório, Deusinete De Oliveira (Zootaxa, 2003)
Five new species of Turbonilla are described from the Brazilian northern continental shelf. Turbonilla virgulinoi n. sp. from off Pernambuco State (690 m depth) is diagnosed by its semi-pyriform profile and sinuous axial ribs. Turbonilla megascymna n. sp. from off Paraíba State (750 m depth) is characterized by its fragile shell and relatively large planispiral protoconch. Turbonilla kamayura n. sp. from off Paraíba State (750 m depth) is diagnosed by its slightly conical shell with convex whorls without spiral sculpture and the helicoidal protoconch. Turbonilla mermeroglaphyra n. sp. from off Alagoas State (255 m depth) has a slightly telescopic shell and is almost straight in profile; axial ribs become obsolete toward the last whorls. Turbonilla aquilonaria n. sp. from Pernambuco State (intertidal) is diagnosed by its tall shell without spiral sculpture and distinctly conical and almost flat-sided teleoconch whorls.